Environmental justice at the intersection: exclusion patterns in urban mobility narratives and decision making in Monterrey, Mexico - Chavez-Rodriguez, Libertad; Treviño Lomas, Raquel; Curry, Laura (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
Placing the urban environment of Monterrey, Mexico at the center of our research, this paper examines how urban mobility intersects with gender and environmental justice. As a transdisciplinary team of scholars, artists, and activists, we examine the urban mobility discourses and discuss how transportation and urban narratives such as sustainable mobility and human cities reinforce: - a car centered dominant narrative that maintains environmental and mobility injustices, - the socio-spatial segregation, exclusion, and accelerated gentrification processes in Monterrey. And, we discuss how these narratives exclude queer and feminist perspectives and their bodies. Using official and media reports we look at how the political and economic elites use narratives to prop up an imaginary of urban equality as part of a walkable and/or cycling city. These narratives maintain a status quo that includes new housing and transportation construction as part of an ongoing unjust system that we refer to as intersectional, in regards to gender, racism, socio-economic status, and age. We conclude environmental justice can only be achieved with mobility justice and that to achieve mobility justice we need to queer the city. To queer a city is when mobility patterns and connectivity of neighborhoods in the periphery are prioritized; when transparency mechanisms, gender perspectives and embodied experiences are the norm, and when aspiration includes achieving a less polluted, sustainable and equitable city.